Zero-field edge plasmons in a magnetic topological insulator. Issue 1 (December 2017) - Mahoney, Alice; Colless, James; Peeters, Lucas; Pauka, Sebastian; Fox, Eli; Kou, Xufeng; Pan, Lei; Wang, Kang; Goldhaber-Gordon, David; Reilly, David
Abstract Incorporating ferromagnetic dopants into three-dimensional topological insulator thin films has recently led to the realisation of the quantum anomalous Hall effect. These materials are of great interest since they may support electrical currents that flow without resistance, even at zero magnetic field. To date, the quantum anomalous Hall effect has been investigated using low-frequency transport measurements. However, transport results can be difficult to interpret due to the presence of parallel conductive paths, or because additional non-chiral edge channels may exist. Here we move beyond transport measurements by probing the microwave response of a magnetised disk of Cr-(Bi, Sb)2 Te3 . We identify features associated with chiral edge plasmons, a signature that robust edge channels are intrinsic to this material system. Our results provide a measure of the velocity of edge excitations without contacting the sample, and pave the way for an on-chip circuit element of practical importance: the zero-field microwave circulator. Direct measurement of edge transport in the quantum anomalous Hall effect can be made difficult due to the presence of parallel conductive paths. Here, Mahoney et al. report features associated with chiral edge plasmons, a signature of robust edge states, by probing the zero-field microwave response of a magnetised disk of Cr-(Bi, Sb)2 Te3 .